EVALUATING USER EXPERIENCE OF THE UNDIKNAS MOBILE APPLICATION WITH USER EXPERIENCE QUESTIONNAIRE (UEQ) - Agustini, Ni Wayan Eva; Sudestra, I Made Ardi; Gunawan, I Made Agus Oka; Indrawan, Gede; Dantes, Gede Rasben; Pidada, Ida Ayu Iswari; Hakimi, Musawer (STKIP PGRI Tulungagung, 2025)
This research aims to evaluate the User Experience (UX) of the Undiknas Mobile application, developed to enhance the academic experience of students at Universitas Pendidikan Nasional (Undiknas). The primary focus of this study is to identify the factors that influence user satisfaction and dissatisfaction, as well as determine the areas that need improvement to enhance the application's UX quality. The research employs the User Experience Questionnaire (UEQ) as the primary tool to assess six key dimensions of user interaction: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. Data were collected from 309 respondents, consisting of students from the 2021 cohort of Universitas Pendidikan Nasional (Undiknas), specifically those in their final semester with more experience in using mobile applications. The respondents were selected to ensure that the data collected is valid and representative. The results show that the application achieved average scores of 1.20 for Attractiveness, 1.34 for Perspicuity, and 1.19 for Stimulation, all of which indicate above-average ratings. However, the Efficiency aspect received a lower score of 0.82, and Novelty scored only 0.73, suggesting that these areas need improvement, particularly in enhancing the app’s speed and adding innovative features. These findings indicate that improving the UX design, with a focus on boosting speed and introducing new features, could significantly enhance user satisfaction and engagement. This research provides valuable contributions to the development of digital academic services in Indonesian higher education, offering insights that can be applied to improve the mobile application's interface and functionality.